Parties & potions [compact disc, unabridged] - Mlynowski, Sarah (Random House/Listening Library, 2009)
High school sophomore Rachel and her younger sister Miri, both witches, are introduced to a wider community of witches while grappling with the problem of whether or not to reveal their powers to their school friends, father, and step-mother.